MODAL SOSIAL KERUKUNAN TIGA AGAMA DI BLINGOH PESISIRAN JEPARA - A. Zaenurrosyid dan M. Zaki Fuad (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2018)
Nowadays, social capital is a determinant factor of success in social development, being an alternative to an optimized community empowerment. Moreover, a very communal society with rich values will be highly supported by the dynamics of development and the strengthening of its social capital. This study attempts to scrutinize social capital of three religions in the Blingoh coast of Jepara, focusing on how religious harmony is established in the area and what is the social capital behind it. This article is a field research using a qualitative approach with descriptive analysis where the data are collected through in-depth interview, observation, and documentation. The research finds that the social capital in the Blingoh coast of Jepara consist of social trusts, a sense of kinship beyond religious boundaries, and the role of interreligious forum of communication. These three factors are pivotal factors in sustaining religious in Blingoh Village.Key words: Social Capital, Religious Harmony, Social Harmony